KAJIAN FINANSIAL AGROINDUSTRI IKAN ASAP DI KECAMATAN BULAK KOTA SURABAYA - Dini Oktavira Wijaya; Teguh Soedarto; Wahyu Santoso (Agrienvi: Jurnal Ilmu Pertanian, 2021)
Entrepreneurs have long attempted smoking Fish in Bulak Subdistrict, but still unknown financial calculations such as business feasibility and smoked fish entrepreneurs do not yet know the development of businesses. This study aims to: Analyze the financial feasibility of Smoked Fish in Bulak Subdistrict. This study showed that: The average value of NPV for smoked fish business is Rp 117,130,729. At the same time, the average value of IRR for smoked fish business in Bulak district is 61%. The average value of BEP rupiah smoked fish in the Bulak sub-district is Rp. 108,452,092. The average value of the BEP Smoked Fish Unit in Bulak Subdistrict is 50,554 units.